2002
DOI: 10.1002/app.11451
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of a new rubbery nanocomposite: Polyepichlorohydrin/organoclay nanocomposites

Abstract: Nanocomposites of organophilic montmorillonite clay (OMMT) and polyepichlorohydrin (PECH) were intercalated by a solvent-casting method using dichloromethane as a solvent. The intercalation of PECH segments in the interlayers of the clay was confirmed by X-ray diffraction, and the intercalation spacing was calculated. The increase in the onset temperature of the thermal degradation indicated the enhancement of thermal stability of PECH due to intercalation. Rheological properties of the PECH/OMMT nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 79 publications
3
17
0
Order By: Relevance
“…Data to demonstrate that were provided with an OC (Mt/octadecyltrimethylammonium) in BR [77] and with another OC (Mt/dimethyl hydrogenated-tallow (2-ethylhexyl) quaternary ammonium methylsulfate) in poly(epichlorohydrine) [78].…”
Section: Rheology Of Rcnmentioning
confidence: 99%
“…Data to demonstrate that were provided with an OC (Mt/octadecyltrimethylammonium) in BR [77] and with another OC (Mt/dimethyl hydrogenated-tallow (2-ethylhexyl) quaternary ammonium methylsulfate) in poly(epichlorohydrine) [78].…”
Section: Rheology Of Rcnmentioning
confidence: 99%
“…Polymer/layered silicate nanocomposites have attracted much attention since the researchers at Toyota Central Research Laboratories reported PA6/clay nanocomposites,1 because they exhibit increased modulus and strength, improved heat resistance, outstanding gas barrier properties, and decreased flammability relative to the polymer matrixes. In the open literature, primarily three kinds of preparation methods for the rubber matrix nanocomposites have been reported: latex,2–8 solution9–12 and melt compounding 12–20. Among the three methods, the latex route is the most promising due to the fact that pristine clay can be used directly, whereas melt compounding, a conventional processing method, is preferred for commercial nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving the melt compounding method reported in the literature were mainly focused on a certain rubber matrix, such as polyepichlorohydrin,11 acrylonitrile‐butadiene rubber (NBR),13,14 EPDM,15,16 and NR 18–20. Unfortunately, these studies did not address such issues as how the formed structure was affected by the characteristics of the rubber when the type of organoclay was given, during which process the formation of nanostructure occurred, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…17 (2010) [481][482][483][484][485][486][487][488][489][490][491][492][493][494] Because of the structural similarity to silica and useful physico-chemical parameters, highly dispersed silicates have become of increasing interest in many industrial branches. Of particular importance are polymer composites filled with modified lamellar silicates [3][4][5][6][7][8][9][10][11][12], whose properties can be controlled by the method of the silicate dispersion in the polymer matrix [13]. Among them much attention has been paid to those of the structure of delaminated composite in which the interactions between the polymer and the filler are the strongest and whose physical and mechanical properties can be controlled in the widest range.…”
Section: Introductionmentioning
confidence: 99%